The Application Of Value For Money In Assessing The Performance Of Public Sector Services At The Regional General Hospital Cahya Batin Kaur District - Astiana, Livi; Arnova, Iwin; Yulianasari, Nina (Utan Kayu Publishing, 2024)
To find out How to Implement Value For Money in Assessing the Performance of Public Sector Services at the Cahya Batin Regional General Hospital, Kaur Regency. This study uses two research methods, namely quantitative and qualitative with the Stewardship theory. This study is associative in nature which aims to determine the relationship between two or more variables, find the role, influence, and causal relationships, namely between the independent variable and the dependent variable. The variables connected in this study are variables consisting of the value for money variable and performance (x) towards public sector services (y). The results of the study showed that the implementation of Value for money was considered satisfactory because it had fulfilled the elements of value for money seen from three aspects, namely the aspect of economization where the cost of services provided was in accordance with the services obtained, the aspect of efficiency of resource utilization had provided quality services and the aspect of the effectiveness of medical and non-medical services provided was comparable to the costs charged. So that the measurement of economic value, efficiency and effectiveness, shows that the performance of the Cahya Batin Regional General Hospital, Kaur Regency has been carried out well and has fulfilled the elements of value for money.